PENGUATAN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL DI ERA REVOLUSI INDUSTRI 4.0 - Lesmana, Deni (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
The rapid development of technology and information in the era of the industrial revolution 4.0 has positive and negative impacts on the world of education, especially students. Improper use actually makes technology have the potential to create new delinquency and crime among teenagers. So that a special character education approach is needed in dealing with this, namely character education with local wisdom. This study uses a descriptive approach with a review of technical literature from various relevant written sources. So as to produce analysis, evaluation and synthesis of knowledge relevant to the expected problem. There are three approaches that can be taken in an effort to strengthen character education based on local wisdom in the era of the industrial revolution 4.0. First, to integrate character education based on local wisdom into subjects. Second, control the school culture. Third, optimizing extracurricular activities.